He Tamariki Kokoti Tau: Whānau of preterm Māori infants (pēpi) reflect on their journeys from birth to first birthday. (30th December 2022) - Adcock, Anna; Cram, Fiona; Edmonds, Liza; Lawton, Beverley
ABSTRACT: An infant arriving early disrupts the birth imaginary of whānau (family collectives) and situates them in unfamiliar health environments that may not be culturally safe. Regaining a sense of familiarity enables whānau to cope with their unexpected preterm trajectory. He Tamariki Kokoti Tau: Babies Born Prematurely was the first Kaupapa Māori prospective qualitative longitudinal study to explore these trajectories, walking alongside whānau from birth to first birthday. This interpretative phenomenological analysis explores the final 'first birthday' interviews with 16 whānau. Concerns that had been raw in early days of neonatal intensive care carried over – frustrating whānau yet strengthening their resolve to support each other. Whānau described how they enacted resilience together, with their whānau collective including health practitioner champions who became 'like whānau' by virtue of their culturally responsive care. While pēpi (infants) continued to experience health issues, whānau felt hopeful for the year ahead. They expressed love, joy, and pride for their pēpi as the centre of their whānau. Whānau are experts of their pēpi, and healthcare champions who recognise this and promote whānau tino-rangatiratanga (autonomy) make a world of difference. Health services can learn from these whānau, about how to better support preterm care pathways for Māori.